MicroRNA-125b: association with disease activity and the treatment response of patients with early rheumatoid arthritis - Hruskova, Veronika; Jandova, Romana; Vernerova, Lucia; Mann, Herman; Pecha, Ondrej; Prajzlerova, Klara; Pavelka, Karel; Vencovsky, Jiri; Filkova, Maria; Senolt, Ladislav (Arthritis research & therapy, 2016)
BACKGROUND: MicroRNAs (miRNAs) are small RNAs that regulate gene expression by targeting mRNA. It was proved that some miRNAs are significantly deregulated in rheumatoid arthritis (RA). MicroRNA-125b negatively regulates expression of TNF-α, which plays a crucial role in RA pathogenesis. The aim of this study was to determine the treatment outcome of patients with early RA based on the expression of circulating and cellular miR-125b. METHODS: Total RNA was isolated from the plasma and peripheral blood mononuclear cells (PBMCs) of 58 patients with early RA before and three months after treatment initiation and of 54 age- and sex-matched healthy controls (HC). The expression of miR-125b was measured by TaqMan quantitative PCR. The treatment responders were defined as patients achieving remission or low disease activity (28-joint count disease activity score (DAS28) <3.2). Receiver operating characteristic (ROC) curve and stepwise backward multivariable logistic regression analyses of miR-125b expression were used to predict the disease outcome at three and six months after initiation of treatment. RESULTS: The expression of miR-125b in the PBMCs and plasma of treatment-naïve early RA patients was significantly lower than that of HC and increased significantly after three months of treatment, particularly in responders. However, only the cellular expression of miR-125b was inversely correlated with disease activity. MiR-125b expression in PBMCs was higher in responders than in non-responders after three months (p = 0.042). Using ROC analysis, the cellular expression of miR-125b, but not the disease activity at baseline, predicted the treatment response after three months of therapy (area under the curve 0.652 (95 % CI 0.510 to 0.793); p = 0.048). CONCLUSION: The expression of miR-125b in PBMCs of treatment-naïve patients may present a novel biomarker for monitoring the treatment outcome during the early phase of RA.
Keywords: senioři; Early rheumatoid arthritis; mikro RNA; výsledek terapie; Middle Aged; ROC Curve; plocha pod křivkou; mužské pohlaví; Adult; ROC křivka; MicroRNAs; ženské pohlaví; Humans; antirevmatika; Disease activity; biologické markery; Arthritis, Rheumatoid; lidé středního věku; Treatment outcome; Area Under Curve; revmatoidní artritida; Antirheumatic Agents; MicroRNA-125b; dospělí; Biomarkers; Female; Aged; Treatment Outcome; lidé; Male